Transforming critical agrarian studies: Solidarity, scholar-activism and emancipatory agendas in and from the Global South - Aguiar, Diana (2023)
This paper examines the challenges and opportunities faced by critical agrarian scholars in and from the Global South. We argue that despite the historical and structural limitations, the critical juncture of convergence of crises and renewed interest in agrarian political economies offers an opportunity for fostering a diverse research agenda that opens space for critical perspectives about, from and by the Global South, which is mostly absent in mainstream scholarship dominated by the Global North. We also propose doing so by enhancing solidarity to transform injustices within academia and other spaces of knowledge production and dissemination. To develop the argument, first, we reflect on the multiplicity of crises in rural areas and the changing character of social struggles, as well as the interlinkages between environmental crises and the re-emergence of critical agrarian studies that are reshaping the agrarian question. Then, we discuss the implications and conditions of the political agenda carried out by a scholar-activist movement working on agrarian studies from the Global South. Drawing on our experience as the Collective of Agrarian Scholar-Activists from the South (CASAS), we conclude by proposing three ways forward for enhancing solidarity through networks of scholar-activists: knowledge accessibility, cooperative organization, and co-production of knowledge.